If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6.3m + 2.7m = 0 Combine like terms: -6.3m + 2.7m = -3.6m -3.6m = 0 Solving -3.6m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-3.6'. m = 0 Simplifying m = 0
| 0.75x+37-2.75=3(4+x) | | 5x-4=8x+12 | | 0.6x=0.5 | | 13x-8=43 | | 6(3x-1)=5 | | 3p-9=30 | | 14-3s=5 | | 4x-x^4=-4 | | 4x+-3=2x+4 | | 4x-4/5=11/5 | | 5q+4(-7+5q)=1-g | | 5x-8=7x-24 | | 5(x+2)=5x+11 | | 14+4k=-2+2k | | y=2x+-7 | | N/5-6=18 | | 1-x=2/5 | | -4n/4=22/3 | | 3x+6x-9=0 | | 4(2x-4)=8x+-16 | | F(x)=13x+3 | | 4=z/9(4y-2) | | 3s-4=5 | | 2(x-1)(4x+3)=0 | | 2/3x-12=2 | | 4x+80=5x+80 | | 5(x+2)-8x=19 | | x=3x+-2 | | 7q-48+3q+6=180 | | -4(b+8)=-25-5b | | 16x^2-96x+48=0 | | 48-n=4*n*7 |